In Vitro Metabolite Formation in Human Hepatocytes and Cardiomyocytes and Metabolism and Tissue Distribution in Monkeys of the 2′-C-Methylguanosine Prodrug BMS-986094: Potential Role in Clinical Cardiovascular Toxicity. (January 2017) - Li, Wenying; Trouba, Kevin J.; Ma, Li; Kwagh, Jae; Storck, Christopher; Zhu, Yongxin; Flint, Oliver; Humphreys, William G.; Wang, Jian; Liu, Ang; Wang, Bonnie; Graziano, Michael J.; et al.
BMS-986094, a 2′-C-methylguanosine prodrug for the treatment of chronic hepatitis C virus infection, was withdrawn from phase 2 clinical trials because of unexpected cardiac and renal toxicities. To better understand these toxicities, the in vitro metabolism of BMS-986094 in human hepatocytes (HHs) and human cardiomyocytes (HCMs) and the measurement of BMS-986094 and selected metabolites in monkey plasma and tissues were assessed. BMS-986094 was extensively metabolized by HHs and HCMs, resulting in more efficient formation and accumulation of the active triphosphorylated metabolite, INX-09114, and less efficient efflux of metabolites in HCMs. The predominant metabolism pathway (hydrolysis) in HHs and HCMs was not associated with the formation of reactive metabolites or oxidative stress. In cynomolgus monkeys dosed with BMS-986094 of 15 or 30 mg/kg/d for 3 weeks, the nucleoside metabolite M2 was the major plasma analyte (66%-68% of the combined area under the curve). INX-09114 was the highest drug-related species in the heart and kidney (2, 610-4, 280 ng/mL [males]; ∼2-420× the concentration of other analytes). Other analytes increased dose dependently, with BMS-986094 highest in diaphragm (≤4, 400 ng/mL) followed by M2 in liver and kidney (≤1, 360 ng/mL), and M7 and M8 in other tissues (≤124 ng/mL). Three weeks after the last dose, INX-09114 remained high in the heart and kidney (≤1, 870 ng/mL), with low M2 (≤37 ng/mL) in plasma and tissues. Persistent high concentrations of INX-09114 in the heart and kidney appeared to correlate with toxicities in these tissues in monkeys.